Inheritance - Lo, Malinda (Little, Brown & Company, 2013)
When teens Reese and David are kidnapped after revealing that they were adapted with alien DNA, Reese is forced to reconcile her new love for David, a human, with feelings for Amber, an Imrian, and make a world-changing choice.